2018
DOI: 10.3389/fimmu.2018.02779
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia longipalpis Saliva Induces Heme Oxygenase-1 Expression at Bite Sites

Abstract: Sand flies bite mammalian hosts to obtain a blood meal, driving changes in the host inflammatory response that support the establishment of Leishmania infection. This effect is partially attributed to components of sand fly saliva, which are able to recruit and activate leukocytes. Our group has shown that heme oxygenase-1 (HO-1) favors Leishmania survival in infected cells by reducing inflammatory responses. Here, we show that exposure to sand fly bites is associated with induction of HO-1 in vivo. Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In skin, heme oxygenases are cytoprotective against reactive oxygen species generated during normal physiological processes, and they limit oxidative stress following exposure to environmental assaults (Szabo et al, 2018). Previously, we have demonstrated that bites of L. longipalpis sand flies induce NFE2L2-dependent production of HO-1 in human skin that was attributed to the effect of saliva (Luz et al, 2018). Here, we show another facet to HO-1 induction in skin triggered by bloodfeeding arthropods.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…In skin, heme oxygenases are cytoprotective against reactive oxygen species generated during normal physiological processes, and they limit oxidative stress following exposure to environmental assaults (Szabo et al, 2018). Previously, we have demonstrated that bites of L. longipalpis sand flies induce NFE2L2-dependent production of HO-1 in human skin that was attributed to the effect of saliva (Luz et al, 2018). Here, we show another facet to HO-1 induction in skin triggered by bloodfeeding arthropods.…”
Section: Introductionmentioning
confidence: 49%
“…Recently, we published that L. longipalpis saliva induces a NFE2L2-dependent production of HO-1 at the site of the bite (Luz et al, 2018). To investigate the contribution of saliva to HO-1 induction at vector bite sites, we compared the intradermal injection of saliva to bites of Lutzomyia sand flies and Aedes mosquitoes ( Figure 1F).…”
Section: Production Of Ho-1 In Host Skin Is a Universal Response To Bmentioning
confidence: 99%
“…Treatment of primary human macrophages with resolvin D1, an important eicosanoid with anti-inflammatory and pro-resolving properties, promotes intracellular L. amazonensis replication through a mechanism associated with induction of HO-1 [108]. It has been proposed that sand fly saliva increases the infection of Leishmania both in vitro and in vivo by modulating several physiological responses of the vertebrate host [106,109]. The ability of sand fly saliva to induce NRF2 and HO-1 in human and mice skin in vivo and on macrophages in vitro, inhibiting the inflammatory response, indicates a previously unappreciated mechanism by which vector saliva affects resistance to Leishmania infection [109].…”
Section: Ho-1 In Leishmaniasismentioning
confidence: 99%
“…It has been proposed that sand fly saliva increases the infection of Leishmania both in vitro and in vivo by modulating several physiological responses of the vertebrate host [106,109]. The ability of sand fly saliva to induce NRF2 and HO-1 in human and mice skin in vivo and on macrophages in vitro, inhibiting the inflammatory response, indicates a previously unappreciated mechanism by which vector saliva affects resistance to Leishmania infection [109]. A recent study showed that patients with higher concentrations of heme in the serum and increased expression of HO-1 have higher parasite burden and a decreased number of neutrophils [110][111].…”
Section: Ho-1 In Leishmaniasismentioning
confidence: 99%
“…A key enzyme triggered by cellular stress is HO-1 (heme oxygenase-1), which exhibits anti-inflammatory, and antioxidant properties, and has a catalytic function that favors Leishmania infection (Luz et al, 2012). Lutzomyia longipalpis Saliva, a type of phlebotomine sandfly, induces macrophages in situ, and in human skin at the bite site to express of Nrf2, and the HO-1 target gene, showing the means by which Leishmania infections are transmitted and established by sandfly-borne vectors (Luz et al, 2018).…”
Section: Nrf2 Pathway In Leishmania Infectionmentioning
confidence: 99%